The course of bacteriological diseases in humans by temperament - Qoziraximova Nargiza Qodirjonovna; Izzatullayeva Dilfuza Ne'matovna; Odilbekova Mahzuna Murodjon qizi (Academia One Publishing, 2023)
This article explores the intriguing relationship between human temperament and the progression of bacteriological diseases. By synthesizing existing literature and employing a multidisciplinary approach, we aim to shed light on how individual temperamental traits may impact susceptibility, severity, and recovery from bacterial infections. The study employs a comprehensive analysis of relevant literature, emphasizing the need for a nuanced understanding of the interplay between temperament and bacteriological diseases. The results may provide valuable insights for personalized healthcare strategies and interventions.
Keywords: Temperament; personalized healthcare; literature analysis